Parallel Aligned Nickel Nanocone Arrays for Multiband Microwave Absorption - Zhang, Wanling; Zhang, Jiaming; Wu, Peng; Chai, Guozhi; Huang, Ran; Ma, Fei; Xu, Fangfang; Cheng, Hongwei; Chen, Yonghui; Ni, Xia; Qiao, Liang; Duan, Jinglai (ACS applied materials & interfaces, 2020)
Magnetic nanostructures with conical shape are highly desired for pursuing extraordinary magnetic properties and microwave absorption. However, the fabrication of such nanostructures with controlled shape and size uniformities and alignment is not yet realized. Accordingly, the magnetic properties and their application as microwave absorber are not well understood. Here, we report on the first demonstration of controlled fabrication of soft magnetic nickel nanocone arrays with sharp geometry, large aspect ratio, uniform size, and parallel alignment. The imaginary part of the relative complex permeability shows multiband absorption in the 2–17 GHz range. Such an exceptional microwave absorption results from the uniform conical shape and size and the parallel alignment. The absorption mechanisms are discussed under the framework of natural resonance and exchange resonance. The natural resonance is dependent on the shape anisotropy and facilitated by the conical geometry. The exchange resonance is well explained by the observation of the bulk spin waves with exchange coupling at the tip of nanocones using the inelastic light scattering and is consistent with exchange theory predictions for the quantization of bulk spin waves. We expect that our work will shed light on the physical insights into the magnetic properties of nanocones and find great potential in applications of microwave absorption.